PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN TOTAL ASET TERHADAP PROFITABILITAS KOPERASI WANITA DI KABUPATEN MADIUN - Fibri Wiranty Nindya Pratiwi; Muhammad Faisal Abdullah; Muhammad Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2018)
The purpose of this study is to determine the effect of working capital turnover, receivable turnover and total asset turnover to profitability in women's cooperatives in Madiun District 2015-2017. This research was conducted on female cooperative in Madiun Regency in 2015-2017. The sample in this study is the financial statements of 14 female cooperatives in 2015-2017. Technical analysis of data in use is panel data regression. Based on the results of the analysis is known that the turnover rate of working capital, receivable turnover and total asset turnover have a positive effect on profitability. The effect of working capital turnover, receivable turnover and asset turnover to profitability have detrmination value of 94.82% while the rest is influenced by other variables not included in the research model.Keywords: working capital turnover, receivable turnover, asset turnover, profitability